(untitled) (Innovate Conferences, 2025)
The research deals with the concept of “Bible” as a religious allusion in one of the short stories written by Somerset Maugham using conceptual integration theory as a tool of investigation. The paper also gives information about informativity theory and its layers that can be decoded throughout the conceptual analysis of religious allusions.